Іміджевий політичний медіатекст. Особливості його функцінування в змі - Гуща, А. А. (ХНУРЕ, 2019)
The concept of «image political media text» combines both PR-texts and advertising texts. This type of text is always initiated by the subject of political activity, contains selective and optimized information. The article presents the genre typology of image political media texts.